2022
DOI: 10.1016/j.jdin.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing use and perceptions of teledermatology: A mixed-methods study of 942 participants

Abstract: Background The protracted COVID-19 pandemic highlights the need for a sustainable telemedicine practice. Objective To understand patient perceptions toward teledermatology. Methods Convergent parallel mixed-methods study of 942 dermatology patients or their caregivers between June 2020 and April 2021. Results Multivariate regression found that youth, increased computer use, willingness to show body areas over photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Effective communication, time, and cost significantly impact patient perspectives on telehealth [7] . Cost of living, traveling, and transportation can be added to the price of health services for patients who need to see their doctors face-to-face.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective communication, time, and cost significantly impact patient perspectives on telehealth [7] . Cost of living, traveling, and transportation can be added to the price of health services for patients who need to see their doctors face-to-face.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as data privacy, emotional factors, and technology culture driving the consultations can influence caregivers' and users’ willingness to use telehealth [7] . For example, Gordon et al [12] emphasized the importance of effective communication with patients during clinical video telehealth appointments to address and answer all patients’ questions as the essential factor influencing their satisfaction with telehealth visits.…”
Section: Qualitative Studymentioning
confidence: 99%
“…Quantitative and qualitative findings were cross-validated for convergence. 2 We found that the willingness to use teledermatology was strongly correlated with barriers, such as the willingness to show images of the body on photo/video and financial costs. In this letter, we provide secondary analysis to build upon the discussion of barriers in the paper by Linggonegoro et al 1 In our data, females and ethnic Malays (who lean religiously conservative) and each individual's concerns over data security and privacy were associated with lower willingness to show body images over photo/video (Table I).…”
mentioning
confidence: 81%
“…We conducted a convergent parallel mixedmethod study to explore the willingness to use teledermatology during the COVID-19 pandemic. 2 Nine hundred forty-two questionnaires and 26 in-depth interviews were administered to dermatology outpatients or their primary caregivers. Questionnaire responses were consolidated and used in multivariable regression analyses, while interview transcripts were coded and analyzed using grounded theory.…”
mentioning
confidence: 99%
“…During this study period, patient portal enrollment was necessary to submit photographs to dermatologists, and this may also contribute to the differences in photograph submission between Black and White patients after adjusting for internet and computer access levels. More broadly, successful enrollment in the electronic patient portal likely represents a patient's overall familiarity with and frequency of technology use, both of which contribute to patients' willingness to participate in video visits [27]. Additionally, the racial differences we have observed likely represent other socioeconomic and infrastructural barriers, such as stable internet connection and personal smartphone or tablet ownership, that were not directly measurable in our study and prevent equitable participation in teledermatology care.…”
Section: Principal Findingsmentioning
confidence: 91%